The effects of unconventional monetary policy on stock markets and household incomes in Japan - Karl-Friedrich Israel; Tim Florian Sepp; Nils Sonnenberg (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2023)
In this study, we investigate the impact of monetary policy on Japanese household incomes using the Family Income and Expenditure Survey. Our analysis focuses on the savings and income structure of households, and covers the period from Q1 2007 to Q2 2021. We find that households in the highest income brackets have a higher proportion of their savings invested in stocks, while middle and lower income households hold a greater share of their savings in bank deposits. Our hypothesis is that the Bank of Japan's monetary policies have boosted stock markets in particular, leading to disproportionate benefits for high-income households through capital gains and dividends. Using local projections, we first identify a positive, lasting cumulative effect of both conventional and unconventional monetary expansion on Japanese stock markets. We then examine how stock market performance impacts household incomes, and find that the effect is strongest for high-income households, decreases for middle-income households, and disappears for lower-income households. Our results suggest that monetary policy may have contributed to the persistent growth in income inequality in Japan, as measured by metrics such as the Gini coefficient and top-to-bottom income ratios.
Keywords: D31; D63; E52; 330; monetary policy; inequality; Japan; household income